Online Positive Interventions to Promote Well-being and Resilience in the Adolescent Population: A Narrative Review - Baños, Rosa M.; Etchemendy, Ernestina; Mira, Adriana; Riva, Giuseppe; Gaggioli, Andrea; Botella, Cristina (Frontiers in Psychiatry, 2017)
Numerous studies have shown an alarming prevalence of depression, anxiety, and behavior disorders in youth. Thus, prevention of psychological problems in this population becomes crucial. According to the World Health Organization (WHO, 2004), prevention should also include the promotion and development of the individual’s strengths in order to reduce vulnerability to suffering from mental disorders. In addition, other key elements of prevention are the reach, adoption, implementation, and maintenance of interventions. The Information and Communication Technologies (ICTs), especially the Internet, have much to offer in terms of the prevention and promotion of positive mental health in adolescents. This paper reviews these fields of research - prevention, positive psychology, Internet, and adolescents- and discusses the potential of positive interventions delivered over the Internet as effective and sustainable health promotion tools. The paper provides a brief description of the systems developed so far and a summary of selected features of the studies detected in the literature review. The overall conclusions are that there is a need for more controlled studies with long-term follow-ups, the interventions should be designed considering the specific features of the target users and the specific contexts where the interventions will be delivered, and they could be enhanced by the use of other technologies, such as smartphones, sensors, or social networks.